Determination of Levels of Iron (Fe) and Mercury (Hg) in Atomic Absorption Spectrophotometry (AAS) in Outlet Waste Water - Sari, Risma; Gusvita, Nola; Nizar, Umar Kalmar; Banon, Charles (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
Wastewater is a contemporary problem as population density increases. Every household living in urban areas will definitely need a waste water disposal site. This research was conducted to determine the levels of iron and mercury. This is done to ensure that the levels of ferrous metal and mercury in the outlet comply with predetermined requirements. The side effect of metal iron and mercury is that if the outlet contains too many levels, the outlet cannot be channeled directly to residential areas, which if released can endanger the health of the community. Quantitative tests were carried out to determine iron content using the flame atomic absorption spectrophotometry method at a wavelength of 248.3 nm and to determine mercury content using the Mercury Vaporizer Unit (MVU) method using atomic absorption spectrophotometry at a wavelength of 253.7 nm. The results of testing for ferrous metal levels in the outlet sample were 0.1969 mg/L. Meanwhile, the mercury level in the outlet sample was 0.0012 mg/L, based on Minister of Environment and Forestry RI No. 05 of 2014 it can be concluded that the levels of ferrous metal (Fe) and mercury (Hg) contained in the outlet wastewater are below the established environmental quality standards.